European PanCareFollowUp Recommendations for surveillance of late effects of childhood, adolescent, and young adult cancer. (September 2021) - van Kalsbeek, Rebecca J.; van der Pal, Helena J.H.; Kremer, Leontien C.M.; Bardi, Edit; Brown, Morven C.; Effeney, Rachel; Winther, Jeanette F.; Follin, Cecilia; den Hartogh, Jaap; Haupt, Riccardo; Hjorth, Lars; Kepak, Tomas; et al.
Abstract: Background: Long-term follow-up (LTFU) care for childhood, adolescent, and young adult (CAYA) cancer survivors is essential to preserve health and quality of life (QoL). Evidence-based guidelines are needed to inform optimal surveillance strategies, but many topics are yet to be addressed by the International Late Effects of Childhood Cancer Guideline Harmonization Group (IGHG). Therefore, the PanCareFollowUp Recommendations Working Group collaborated with stakeholders to develop European harmonised recommendations in anticipation of evidence-based IGHG guidelines. Methods: The PanCareFollowUp Recommendations Working Group, consisting of 23 late effects specialists, researchers, and survivor representatives from nine countries, collaborated in the first Europe-wide effort to provide unified recommendations in anticipation of evidence-based guidelines. A pragmatic methodology was used to define recommendations for topics where no evidence-based IGHG recommendations exist. The objective was to describe the surveillance requirements for high-quality care while balancing the different infrastructures and resources across European health care systems. The process included two face-to-face meetings and an external consultation round involving 18 experts from 14 countries. Results: Twenty-five harmonised recommendations for LTFU care were developed collaboratively and address topics requiring awareness only (n = 6), awareness, history and/or physical examination (n = 9), or additional surveillance tests (n = 10). Conclusions: The PanCareFollowUp Recommendations, representing a unique agreement across European stakeholders, emphasise awareness among survivors and health care providers in addition to tailored clinical evaluation and/or surveillance tests. They include existing IGHG guidelines and additional recommendations developed by a pragmatic methodology and will be used in the Horizon 2020–funded PanCareFollowUp project to improve health and QoL of CAYA cancer survivors. Highlights: Long-term follow-up care is important for survivors of childhood cancer. Evidence-based guidelines to direct care are essential, but lacking for many topics. We developed harmonised surveillance recommendations to bridge the gap. Survivor representatives were involved in the formulation of recommendations.